Legal liability for offenses in the field of nature protection in the first years Soviet authority and times of NEP - Suhorebra, Tetiana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2022)
The article examines the process of establishing administrative responsibility, which was regulated in the Land Code of 1922, the Forest Law of 1923, the Administrative Code of 1927, the Mining Code 1928, in the first years of Soviet power and the times of the NEP. Measures of administrative responsibility in the form of fines, seizure of land plots and transfer to other users, and payment of fees were considered, depending on the type of infringement and the amount of damage caused. Based on the results of the research, the following conclusions can be drawn: 1. Administrative responsibility in the field of nature protection was reflected in the content of the Administrative Code of the Ukrainian SSR of 1927, which contained provisions regarding the protection of forests, parks, squares, the fight against damage to crops, meadows and pastures, and violation of hunting and fishing rules. At that historical period, the Administrative Code of the USSR was the only document adopted in Europe, except for Portugal, which was effective on the territory of a specific state. A characteristic feature of the codified act was the presence of a significant number of articles devoted to administrative violations in the field of forest protection. 2. It is shown that the development of administrative responsibility in the field of land protection took place according to a complex scenario, due to the fact that acts adopted in Soviet Russia and the USSR, which underwent transformation in connection with the transition to the NEP policy, were in force in this field. The foundations of responsibility in this area were laid by the Decree "On Land", adopted on October 25, 1917. The Land Code of the USSR of 1922 established such norms of administrative responsibility for offenses as the imposition of fines, the termination of the right to use land, and the seizure of land plots. 3. In that historical period, considerable attention was paid to the protection of subsoil on the basis of the Mining Code of 1928, which established the norms of administrative responsibility for violations of the established rules and instructions related to illegal development, livestock, prospecting, exploration, extraction and processing operations natural mines. 4. Administrative responsibility in the field of forest protection was regulated in the Law on Forests of the USSR of 1923, the content of which was influenced by the norms of pre-revolutionary law and the Forest Charters of the Russian Empire, which defined the composition of offenses and introduced a system of fees and fines. The law "On Forests of the Ukrainian SSR" established responsibility for illegal felling of forests, setting fire to forests, spoiling them with cattle and carrying out secondary forest use without permission, and provided for incentives for forest guards to apprehend offenders.